Average diagonal entropy in nonequilibrium isolated quantum systems - Giraud, Olivier (2016)
The diagonal entropy was introduced as a good entropy candidate especially for isolated quantum systems out of equilibrium. Here we present an analytical calculation of the average diagonal entropy for systems undergoing unitary evolution and an external perturbation in the form of a cyclic quench. We compare our analytical findings with numerical simulations of various quantum systems. Our calculations elucidate various heuristic relations proposed recently in the literature.